Regulation of copper homeostasis in plants: a focus on chloroplastic superoxide dismutases and copper delivery mechanisms - Cohu, Christopher Michael, author; Pilon, Marinus, advisor (Colorado State University. Libraries, 2009)
Copper (Cu) is an essential micronutrient for higher plant growth and is found in proteins that are important in photosynthesis and respiration. As a cofactor, this trace element is associated with many proteins including plastocyanin, Cu/Zn superoxide dismutase (Cu/ZnSOD), and mitochondrial cytochrome- c oxidase. Due to its redox-active role, Cu is essential for plant life, yet Cu is also dangerous as a free cellular ion and even toxic if in excess. Therefore, delivery and sequestration of Cu must be tightly regulated. The research of this dissertation indicates that sensory mechanisms and signaling pathways exist to coordinate Cu transport and target protein expression based on Cu status. For Arabidopsis and crop species, chloroplastic Cu/ZnSOD is down-regulated during limited Cu availability while at the same time FeSOD is up-regulated. During Cu-limited growth, when Cu/ZnSOD is down-regulated, plastocyanin levels do not change. We suggest that this reduction in Cu/ZnSOD allows for preferential Cu delivery to plastocyanin, which is essential for photosynthesis, while also maintaining chloroplast SOD activity. Cu delivery to Cu/ZnSOD is accomplished by the Cu Chaperone for SOD (CCS). When a CCS loss of function mutant was grown on Cu supplemented soil Cu/ZnSOD and FeSOD activity was not detected. Chloroplast did not exhibit an observable phenotype or photosynthetic deficiencies, even after high light stress treatments. Recent studies have shown that Cu/ZnSODs in the cytosol and chloroplast, along with other Cu proteins, are regulated by Cu via microRNA directed cleavage of Cu protein mRNA. It has also been determined that during Cu-limited growth the SPL7 transcription factor plays a central role in activating Cu-microRNAs and possibly Cu transporters. The research of this dissertation indicates that CCS is also regulated by Cu, mediated by microRNA398, which was not previously predicted by bioinformatic algorithms. Furthermore, data is presented to suggest that SPL7 likely regulates the promoter of FeSOD by activating transcription during limited Cu availability.
Keywords: chloroplastic superoxide dismutases; copper homeostasis; plastocyanin; microRNAs; plant biology